2013
DOI: 10.1088/0957-4484/24/4/045102
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes enhance the internalization of drugs by cancer cells and decrease their chemoresistance to cytostatics

Abstract: Etoposide is a semisynthetic, chemotherapeutic drug widely recommended to treat an extensive range of human cancers. Our studies indicate that, while etoposide is capable of killing human cancer cells, exposure to single-walled carbon nanotubes (SWCNTs) and etoposide results in enhanced cell death that appears to be synergistic and not merely additive. In this study, we used high pressure liquid chromatography and mass spectrometry to quantify the internal effective dose of etoposide when the human pancreatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 43 publications
3
18
0
Order By: Relevance
“…It was found that "drug-nanotube" hybrids landed, pierced, or in a few cases penetrated cancer cells, similar to our previous studies [42], and the fluorescent drugs were unloaded intracellularly, mainly by diffusion after enzymatic cleavage or physical unloading. The enhanced cell penetration by nanotubes, also in the presence of magnetic field and noncytotoxic to human monocyte macrophage cells, was described by Boncel et al [42] and Mahmood et al [55]. The latter complex mechanism opens an additional route of intracellular release in the presence of a magnetic field.…”
Section: Drugs and "Drugmentioning
confidence: 80%
“…It was found that "drug-nanotube" hybrids landed, pierced, or in a few cases penetrated cancer cells, similar to our previous studies [42], and the fluorescent drugs were unloaded intracellularly, mainly by diffusion after enzymatic cleavage or physical unloading. The enhanced cell penetration by nanotubes, also in the presence of magnetic field and noncytotoxic to human monocyte macrophage cells, was described by Boncel et al [42] and Mahmood et al [55]. The latter complex mechanism opens an additional route of intracellular release in the presence of a magnetic field.…”
Section: Drugs and "Drugmentioning
confidence: 80%
“…In addition to facilitate a passive targeting, various studies have demonstrated that carbon nanomaterials can also act as anti-tumor agents themselves and sensitize cancer cells to cytotoxic drugs such as etoposide [23–24 26], dexamethasone [23], paclitaxel [25] and CDDP [16]. In accordance, we have previously shown that CNFs and multiwalled CNTs could enhance the anti-proliferative and pro-apoptotic effects of CDDP and CP in prostate and bladder cancer cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, synergistic increases of the expected effects of 1.3-, 1.4- and 1.6-fold could be observed for the combinations CNFs–DTX (cell colony formation), CNFs–MMC (cell death rate) and CNFs–CP (cell death rate), respectively (Table 3). Furthermore, other studies have also demonstrated that single-walled CNTs can augment the effectiveness of cytotoxic drugs such as etoposide and paclitaxel via enhanced apoptosis [24–26]. The single-walled CNTs have been applied in concentrations of up to 20 ”g/mL in these studies [24–26], whereupon one has to bear in mind that single-walled CNTs are more toxic than multiwalled CNTs [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similarly pioneering study, Huang et al used DFM to show the preferential binding of Au nanospheres and nanorods to cancer cells over healthy cells after functionalization of the NPs with a targeting moiety [85]. Both these studies, among others [107], have applied DFM mostly as a qualitative technique to confirm the presence, and approximate abundance, of the NP of interest. However, as is often the case with microscopy, extracting quantitative characterization data about the state of NPs in biological fluids can be challenging.…”
Section: Spectroscopic and Microscopy Methods (Table 2)mentioning
confidence: 99%